An Undemocratic Guardian of Democracy - International Human Rights Complaint Procedures - Hamamoto, Shotaro (Victoria University of Wellington Law Review, 2007)
This paper discusses the individual complaints procedures established pursuant to international human rights treaties such as the International Covenant on Civil and Political Rights. It discusses the bases on which these systems have been criticised as undemocratic. After considering how these democratic failings could be ameliorated through greater involvement of domestic parliaments, it questions this narrow view of democracy that looks only to parliamentary involvement, suggesting instead that apparently undemocratic individual complaints procedures can actually have a beneficial "democratising" effect.